Influence of orthodontic treatment on root resorption: a systematic review (Revista da Faculdade de Odontologia - UPF, 2016)
Objective: To perform a systematic review relating the existence of root resorption during orthodontic treatment. Methods: The research was performed in two electronic databases (PubMed and OpenGrey). The OpenGrey database was used exclusively for searching the “grey literature”, avoiding selection and publication bias. Eligibility criteria included full texts available online, but with no language restriction. Aiming to work with more current articles on the subject, a filter for thelast ten years was applied. Articles that had no direct relation with the main outcome of this study were excluded, as well as clinical case reports and opinions, literature review articles, editorials, and letters to the editor. All eligible studies were assessed for risk of bias and individual quality, and all research steps were performed independently by two eligibility reviewers. Results: Initially, 77 articles were selected, but after the application of exclusion criteria, only 71 were included. Six articles were eligible for qualitative assessment. Overall, incisors are the teeth most affected by root resorption and there is a higher rate of root resorption in retraction mechanics. Conclusion: There is a relationship between root resorption and orthodontic treatment.